The impact of the identification process and the corporate social responsibility process on the effectiveness of multi-racial advertising in South Africa - Johnson, Guillaume Desire (Rhodes University, Faculty of Commerce, Department of Management, 2008)
Selecting actors to appear in an advertisement is an important decision which has a crucial impact on the effectiveness of an advertising campaign. The same message, delivered by different actors, produces varying outcomes among consumers. This dilemma concerning the choice of actors occurs particularly in multi-racial societies, such as South Africa, where advertisers have to target different sectors of the community. In multi-racial societies, the choice of actors in advertisements goes beyond the usual commercial reasons. Indeed, two dimensions are generally conferred to multi-racial advertising. Firstly, the use of multi-racial representations allows for the targeting of a wider population that also owns a wider purchasing power. Marketers who want to market their brand use, for example, white and black actors so that white and black consumers can identify with the actors and recognize themselves as the target of the advertisement. Secondly, the multi-racial representations of this type of advertising hold a social role that counteracts the segregated depiction of the society. Consumers who are exposed to a multi-racial advertisement might perceive this social dimension and attribute a social responsibility to the advertisement. The purpose of this thesis is to examine the influence of the above dimensions on the effectiveness of a multi-racial advertisement. On the one hand, this study investigates the Identification Process followed by a consumer exposed to a multi-racial advertisement. On the other hand, it examines how consumers attribute a social responsibility to a specific multiracial advertisement and how this attribution, in turn, influences their responses to the advertisement and brand. Finally, the impacts of both of these dimensions on consumer behaviour are compared and the most persuasive dimension is identified. This thesis draws on Attribution Theory and Identification Theory in arguing that there are strong economic imperatives for adopting a multi-racial advertising approach. The thesis develops a conceptual framework and tests empirically hypotheses regarding the key constructs and moderating variables. The empirical results point out that both dimensions symbiotically influence the effectiveness of a multi-racial advertisement. Specifically, the results highlight that the social responsibility attributed by the viewers to the advertisement influences their behaviour more than the Identification Process.
Keywords: Marketing -- South Africa; Advertising -- South Africa; Sales promotion -- South Africa; Consumers' preferences -- South Africa; Marketing research -- South Africa; Consumer behavior -- South Africa; Consumption (Economics) -- Social aspect; Attribution (Social psychology); South Africans -- Race identity; Race awareness -- South Africa; Ethnopsychology -- South Africa; Group identity; Racially mixed people